Platelet disorders in uraemia before and after haemodialysis under the influence of low dose aspirin - Tschugguel, Walter; Blaicher, Alex; Kramer, Ludwig; Felfernig, Michael; Jüngling, Gerhard; Kurz, Martin; Gnant, Michael; Zimpfer, Michael (Thrombosis research, 1995)
Thrombocyte dysfunction and increased bleeding time (BT) are well documented in uraemic patients. However, these patients are frequently medicated with low dose aspirin (ASA) in order to maintain shunt patency and prevent cardiovascular events. Recently, life- threatening gastrointestinal haemorrhage in an uraemic subject taking low dose aspirin has been reported. In this work ASA related bleeding risk in uraemic patients and the effect of haemodialysis on their bleeding tendency was studied by measuring in vitro bleeding time (BT) using the Thrombostat 4000® in 34 uraemic patients on chronic haemodialysis compared to 50 healthy subjects. Our results indicate that low dose aspirin does not influence uraemic thrombopathia 8 to 10h after ingestion but seems to increase bleeding risk shortly after ingestion. Moreover, haemodialysis alters uraemic in vitro BT with regard to the time after ingestion of ASA.